ONLINE NUCLEAR ORIENTATION OF CESIUM ISOTOPES AND THE MAGNETIC-MOMENT OF CS-118M - Shaw, T; Green, V; Ashworth, C; Rikovska, J; Stone, N; Walker, P; Grant, I (1987)
Cesium isotopes have been oriented in iron, following on-line implantation at temperatures down to 8 mK. Analysis of results on transitions in the decay of Csm119, Csg120, and Csm121 yields the hyperfine field Bhf(CsFe)=(+)40.8(7) T. A repeated sequence of short pulse implantation followed by relaxation has been used to measure the Korringa constant, CK=0.059(15) K s for Csm121 in iron. The magnetic moment of Csm118 (T1/2=17 s), previously unknown, is deduced to be e e =5.4(11) N, which identifies the presence of the g9/2 intruder Nilsson orbital. © 1987 The American Physical Society.